Hubungan antara kadar homosistein (Hcy) dengan kejadian ketuban pecah dini (KPD) pada kehamilan preterm - Agrifa Eko Albert Sembiring; Tjokorda Gde Agung Suwardewa; Ketut Surya Negara; I Nyoman Gede Budiana; Ida Bagus Putra Adnyana; Evert Solomon Pangkahila (DiscoverSys Inc., 2022)
Background: Premature rupture of membranes (PROM) has been a problem in obstetrics since ancient times until now. The incidence of PROM in the world ranges from 5% - 15% of all pregnancies, while the incidence in developing countries, especially Indonesia ranges from 4.5% to 7.6% of all pregnancies. Preterm is one of the highest contributors to perinatal mortality and morbidity. The incidence of preterm pregnancy in the world is around 9.6% of all births, while in Southeast Asia is around 11.1% It has been shown to have a significant effect on vascular endothelial pathology. Methods: The study was conducted with an analytic cross-sectional design involving 70 respondents of pregnant women with gestational age of 20 - < 37 weeks with and without PPROM who came to the outpatient clinic and maternity ward of Prof. Dr. I.G.N.G. Ngoerah Hospital Denpasar from May 2021 – July 2021. Results: The results of the analysis of this study found a statistically significant relationship between homocysteine (Hcy) levels and the incidence of preterm premature rupture of membranes (p = 0.001). The prevalence ratio value of 2.2 means that high homocysteine levels is a risk factor for premature rupture of membranes in preterm pregnancy (RP = 2.2; 95% CI = 1.33-2.94; p = 0.001). Conclusion: High homocysteine level is a risk factor for premature rupture of membranes in preterm pregnancy. Latar Belakang: Ketuban pecah dini (KPD) preterm merupakan masalah di bidang obstetrik sejak dahulu sampai sekarang. Insiden KPD di dunia berkisar antara 5% - 15% dari seluruh kehamilan. Insiden KPD di negara berkembang khususnya Indonesia berkisar 4,5% - 7,6% dari seluruh kehamilan. Kehamilan preterm menjadi salah satu penyumbang tertinggi angka mortalitas dan morbiditas perinatal. Insiden kehamilan preterm di dunia sekitar 9.6% dari semua kelahiran, sedangkan di Asia tenggara terdapat sekitar 11,1%. Hcy telah terbukti signifikan berpengaruh pada patologi endotel pembuluh darah. Metode: Penelitian dilakukan dengan rancangan cross sectional analitik dengan melibatkan 70 responden wanita hamil dengan usia gestasi 20 - <70 minggu dengan atau tanpa KPD yang dating ke poliklinik dan ruang bersalin RSUP Prof. Dr. I.G.N.G. Ngoerah bulan Mei 2021 – Juli 2021. Hasil: Diperoleh hubungan bermaksana secara statistik antara kadar homocycteine dengan kejadian ketuban pecah dini pada kehamilan preterm (p = 0, 001), dan rasio prevalensi 2,2 berarti kadar homosisteine yang tinggi merupakan faktor risiko terjadinya ketuban pecah dini pada kehamilan preterm (RP = 2.2; 95% CI = 1.33-2.94; p = 0.001). Kesimpulan: Kadar homosistein yang tinggi merupakan faktor risiko terjadinya ketuban pecah dini pada kehamilan preterm.